2014
DOI: 10.1371/journal.pone.0090571
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Produced Matrix Metalloproteinases Are Regulated by CD147 in Liver Fibrogenesis

Abstract: BackgroundThe classical paradigm of liver injury asserts that hepatic stellate cells (HSC) produce, remodel and turnover the abnormal extracellular matrix (ECM) of fibrosis via matrix metalloproteinases (MMPs). In extrahepatic tissues MMP production is regulated by a number of mechanisms including expression of the glycoprotein CD147. Previously, we have shown that CD147 is expressed on hepatocytes but not within the fibrotic septa in cirrhosis [1]. Therefore, we investigated if hepatocytes produce MMPs, regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 65 publications
2
37
1
Order By: Relevance
“…In situ hybridization and immunohistochemistry on tissue sections and primary isolated hepatocytes showed heterogeneous expression of MMP‐2, MMP‐3, and MMP‐13 as well as TIMP‐1 and TIMP‐2 in lobules in CCl 4 ‐induced fibrosis and with fibrosis resolution . This finding was validated by our group as we have found significant expression of MMP‐2, MMP‐9, MMP‐13, and MMP‐14 in human and murine hepatocytes mediated by the glycoprotein CD147 with liver injury . In vitro hepatocytes were shown to be essential for MMP‐2 activation in untreated HSC cultures, and this has been attributed to hepatocyte‐derived MT2‐MMP .…”
Section: The Case For An Accomplice Role For Hepatocytes In Progressisupporting
confidence: 68%
See 2 more Smart Citations
“…In situ hybridization and immunohistochemistry on tissue sections and primary isolated hepatocytes showed heterogeneous expression of MMP‐2, MMP‐3, and MMP‐13 as well as TIMP‐1 and TIMP‐2 in lobules in CCl 4 ‐induced fibrosis and with fibrosis resolution . This finding was validated by our group as we have found significant expression of MMP‐2, MMP‐9, MMP‐13, and MMP‐14 in human and murine hepatocytes mediated by the glycoprotein CD147 with liver injury . In vitro hepatocytes were shown to be essential for MMP‐2 activation in untreated HSC cultures, and this has been attributed to hepatocyte‐derived MT2‐MMP .…”
Section: The Case For An Accomplice Role For Hepatocytes In Progressisupporting
confidence: 68%
“…Degradation of fibrous tissue is accompanied by intrahepatic upregulation of MMP‐1, MMP‐2, and MMP‐8 and downregulation of TIMP‐1 and TIMP‐2 . The cellular origins of the MMPs leading to the resolution of fibrosis are HSCs, inflammatory infiltrate (in particular macrophages), and hepatocytes . Further, apoptosis of activated HSCs is known to be an important factor in the resolution of fibrosis .…”
Section: Current Cellular Model Of Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hepatocytes have been investigated as a source of TIMPs and other matrix modulators protein. Thus, they could play a role in processes of fibrogenesis and fibrosis regeneration 59 . Fibrosis progresses by HSCs, and hepatocyte damage deteriorates 20 .…”
Section: Discussionmentioning
confidence: 99%
“…14 MMPs act as a part of a proteolytic network, in which proteases activate each other by processing inactive proforms. For instance, it has been shown that proMMP-2 is activated by MT-MMP-1 (MMP-14) in complex with TIMP-2, 15 and further MMP-2 and MT-MMP-1 are activated by proMMP-13.…”
mentioning
confidence: 99%